In Vitro Exploration of Healthy and Stressed Gut Microbiota Metabolism (P20-002-19). (13th June 2019) - Soares, Jason; Pantoja-Feliciano, Ida; Doherty, Laurel; Arcidiacono, Steven; Branck, Tobyn; Karl, J Philip; Racicot, Kenneth
Abstract: Objectives: From a military perspective, the gut microbiome serves as an ideal tool to enhance Soldier gut and immune health and to improve survivability and performance. Our work employs in vitro tools as a means to elucidate systematic processes of colonic bacterial metabolism of dietary inputs under native and stressed conditions. This talk will focus on the use of in vitro fermentation to investigate both the prebiotic potential of cranberry proanthocyanidins (PAC) within a healthy microbiome and stress-induced alterations in microbial inter-species competition for fermentable fiber. Methods: Fermentations were performed in triplicate, utilizing fecal inocula derived from at least three individuals, in a nutrient-rich anaerobic medium with sampling at 0 and 24 hrs. Within PAC supplementation studies, samples were analyzed for bacterial identification (16 s rRNA sequencing) and metabolite content (GC-FID and GC/MS). Stressed metabolism studies, which utilized fecal samples before and after a 21-day change in diet challenge (habitual vs. Meal Ready-to-Eat), employed media supplemented with resistant starch under ascending colon domain-specific conditions; samples taken were analyzed for bacterial identification (16 s rRNA) and enumeration of select organisms (qPCR). Results: Bacterial population dynamics within PAC supplementation studies indicated a dose-dependent increase in several beneficial taxa, including Ruminococcus spp ( P  < 0.05). Phenolic metabolite generation as a function of PAC dosage identified several compounds associated with anti-inflammatory activity, including 3-(4-OH-phenyl) propionic acid ( P  < 0.001). Within stressed metabolism studies, Lactobacillus spp. growth was attenuated as a function of sudden change in diet ( P  ≤ 0.001), whereas growth of R. bromii was enhanced ( P  ≤ 0.05), indicating potential for an acute stressor to impact gut bacteria functional metabolism. Conclusions: In vitro fermentation elucidated both a potential prebiotic effect of cranberry PAC on gut microbiota and the impact of sudden change in diet on inter-species competition for nutritional substrates. Understanding of gut microbiota metabolism dynamics could direct future dietary supplementation strategies to build resiliency against military-relevant stressors and offset negative impacts of dysbiosis. Funding Sources: Defense Health Program.